Utilizing sense and respond methods to predict market requirements in an erratic business environment - Heikkilä, Tomi (My University, 2014)
The global business environment constantly changes regardless of the branch of industry. Changes in the business environment and market requirements present both opportunities and threats for companies. Future success will be a result of today’s investments in resources and capabilities. The major challenge for companies is to define the correct targets and priorities for investments to achieve competitive advantage in the future. To achieve long–term success, sensing market requirements and generating correct responses is vital. Another huge challenge for companies is therefore to find the means to make meaning from the unclear noises and signs coming from the erratic market. This research is focused on the global service business, with the purpose of providing and interpreting information from the rapidly changing environment. The research is based on the sense and respond methods developed at the University of Vaasa. These methods were developed to gather and analyse information from the environment and support companies in decision–making and resource allocation. Data for the research is collected from external and internal stakeholders with a tailor-made online questionnaire. In addition, data from previous interview surveys at a case company is used. Both quantitative and qualitative research is included to maintain high validity and reliability. The results are validated through a weak market test built in collaboration with the case company’s decision–makers. The results are proven to be reliable, which indicates that sense and respond methods have the potential to be a valuable tool for predicting and analysing current and future market requirements.
Keywords: Predictive analytics; future foresight; sense and respond; satisfaction measurement; operational competitiveness; fi=Tuotantotalous|en=Industrial Management|